Analisis Hukum Terhadap Tanggung Jawab Sosial Perusahaan (Corporate Social Responsibility) dalam Perspektif Hukum Indonesia: Penelitian - Nana Kartika; Siti Nur Raihani; Tia Nazla Ramadhani; Joito Rajagukguk; Yola Fifilyan Salam (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Corporate Social Responsibility (CSR) is a concept that views companies not merely as profit-seeking business players, but also as legal entities with social responsibilities and a strong commitment to the environment. This research aims to find ways to implement CSR, define the various social responsibilities that companies must undertake, and discuss the legal regulations in Indonesia that govern CSR. The method used is normative legal research, which involves analyzing existing regulations and employing a conceptual approach. The results show that CSR implementation in companies occurs through three interrelated main stages: planning, implementation, and reporting. All stages are directly integrated into company policy. Furthermore, this form of corporate social responsibility encompasses three main aspects: social, economic, and environmental. The provisions regarding these three aspects are clearly explained in various laws and regulations in force in Indonesia.